Vulnerability assessment and penetration testing in the military and IHL context - Mladenović, Dragan D. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Vulnerability assessment and penetration testing are the key activities of information security risk management and cyber defense and intelligence done by military organizations. These activities are significant not only in the context of performing military operations, but also in the International Humanitarian Law (IHL) and law enforcement contexts. The application of information technologies in the military and civilian environments increases complexity in the field of risk management. Besides information security, military organizations have the task to undertake necessary activities in the fields of cyber operations, both for defense and offense purposes. They depend on technologically based knowledge and skills and are implemented by specific organizations within military systems. The goal of vulnerability assessment is to discover and determine the nature of vulnerabilities, without considering how they may be used for offense, while penetration testing uses exploits for breaching into systems and thus estimates the type and degree of risk these vulnerabilities represent to the system. However, even if they represent two different activities, with different end goals but the same field of interest, they are complimentary and inter-dependent. Since their common feature is development of knowledge and skills based on the same technologies, they are equally important both for risk management, military operations in cyberspace and their use for defense and intelligence activities as well as for IHL.